Tectorigenin: A Review of Its Sources, Pharmacology, Toxicity, and Pharmacokinetics - Juan Rong; Fei Fu; Chenxia Han; Yaling Wu; Qing Xia; Dan Du (Molecules, 2023)
Tectorigenin is a well-known natural flavonoid aglycone and an active component that exists in numerous plants. Growing evidence suggests that tectorigenin has multiple pharmacological effects, such as anticancer, antidiabetic, hepatoprotective, anti-inflammatory, antioxidative, antimicrobial, cardioprotective, and neuroprotective. These pharmacological properties provide the basis for the treatment of many kinds of illnesses, including several types of cancer, diabetes, hepatic fibrosis, osteoarthritis, Alzheimer’s disease, etc. The purpose of this paper is to provide a comprehensive summary and review of the sources, extraction and synthesis, pharmacological effects, toxicity, pharmacokinetics, and delivery strategy aspects of tectorigenin. Tectorigenin may exert certain cytotoxicity, which is related to the administration time and concentration. Pharmacokinetic studies have demonstrated that the main metabolic pathways in rats for tectorigenin are glucuronidation, sulfation, demethylation and methoxylation, but that it exhibits poor bioavailability. From our perspective, further research on tectorigenin should cover: exploring the pharmacological targets and mechanisms of action; finding an appropriate concentration to balance pharmacological effects and toxicity; attempting diversified delivery strategies to improve the bioavailability; and structural modification to obtain tectorigenin derivatives with higher pharmacological activity.